Mengapa Takut Ketinggalan Bisa Membuat Kita Kecanduan Game Online? - Anisa Resa Savitri; Aggio Malvino; Ayu Anjelina; Kania Jeanrita; Rani Sagita; Tesa Anggraini; Zuliana Wijaya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
This study aims to explore the relationship between FoMo (Fear of Missing Out) and online game addiction among students in West Sumatra aged 18-25 years. The method used is quantitative with purposive sampling technique and the research subjects amounted to 200 people. Data collection was carried out through a questionnaire that measured FoMo and online game addiction. The results showed that 97% of respondents were in the high online game addiction category, of which 35.5% were in the 21-year-old age group as the most vulnerable population. Data analysis using linear regression showed a positive correlation between FoMo and online game addiction (Pearson coefficient = 0.188, p = 0.004). The R square value of 0.035 indicates that FoMo contributed 3.5% to online game addiction, while 96.5% was influenced by other factors. These findings indicate that FoMo has a significant role in driving online game addiction behavior, although its contribution is relatively small.